Dampak Financial Technology (Fintech) dalam Meningkatkan Aksesibilitas dan Keberlanjutan Keuangan pada Perbankan Syariah - Yuniar Tri Hidayah; Imron Rosyadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the influence of financial report accessibility and sustainability reporting on the implementation of financial technology (fintech) in Islamic banking in Indonesia. A causal-comparative method with a quantitative approach was employed. The independent variables include financial report accessibility, measured using Return on Equity (ROE), and sustainability reporting, assessed using a sustainability report disclosure index. The dependent variable is fintech, categorized by digital service types such as mobile banking and internet banking. Data were collected from Islamic banking financial statements listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period using purposive sampling based on specific criteria. The results reveal that both financial accessibility and sustainability reports significantly influence fintech adoption. This indicates that higher access to financial information and stronger sustainability commitments increase the likelihood of Islamic banks adopting fintech as part of their efficiency and service innovation strategy.